2010
DOI: 10.1007/s00701-010-0650-5
|View full text |Cite
|
Sign up to set email alerts
|

Favourable long-term clinical outcome after anterior cervical discectomy. A study on a series of 125 patients undergoing surgery a mean of 11 years earlier

Abstract: In our series, 96% of patients had a sustained favourable long-term clinical outcome after ACD. These favourable results confirm data in the literature and support our preference for ACD as the simplest, fastest and cheapest surgical option for treating myeloradiculopathy secondary to one- to two-level cervical discoarthrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…In fact, it appears that disc space destruction correlates with spontaneous fusion. ACD leads to spontaneous bony fusion in 70-90 % of cases [17,18] as a result of ongoing degeneration, which is assumed to be related to long-term deterioration of the clinical outcome [19]. Although there is no direct comparison with ACD, AF seems to induce less same-level degeneration, much less spontaneous fusion, and thus less long-term deterioration in the clinical outcome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it appears that disc space destruction correlates with spontaneous fusion. ACD leads to spontaneous bony fusion in 70-90 % of cases [17,18] as a result of ongoing degeneration, which is assumed to be related to long-term deterioration of the clinical outcome [19]. Although there is no direct comparison with ACD, AF seems to induce less same-level degeneration, much less spontaneous fusion, and thus less long-term deterioration in the clinical outcome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As far as patients with degenerative changes in the cervical segment are concerned, Faldini [48] noticed that up to 75% of patients evaluated the results of treatment as good or excellent. Another study showed that the success rate can be even higher, with 96% of patients reporting improvement [49]. Such promising results may predominantly arise from shorter duration of pain symptoms prior to the procedure, particularly in the context of nerve root pain [50].…”
Section: Discussionmentioning
confidence: 99%
“…Faldini et al reported a series of 51 patients treated with anterior cervical discectomy and fusion followed for 10 years noting that over 75% of patients rated their outcome good to excellent according to Odom's criteria [30]. Another study of 125 patients followed for 11 years on average indicated a 96% favorable outcome with only 5 patients undergoing adjacent level surgery [31].…”
Section: Surgical Treatment Of Radiculopathymentioning
confidence: 97%